2022
DOI: 10.3389/fphys.2021.794721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Nutritional Conditions on the Growth and Reproduction of Nilaparvata lugens (Stål)

Abstract: Growth and reproduction are the two most basic life processes of organisms and the distribution of energy in these processes is a core issue of the life history of organisms. Nilaparvata lugens (Stål), the brown planthopper (BPH), is a single-feeding rice pest. In the present study, this species was used as a model for testing the effects of nutritional conditions on various growth and reproduction indicators. First, the third-instar nymphs were fed with three different concentrations (100, 50, and 25%) of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Pooraiiouby et al (2018) found that a high‐carbohydrate food source significantly induced the expression of ILP3 in A. aegypti and increased the storage of nutrients to enhance the fecundity of female mosquitoes. Similarly, under high‐nutrient concentrations, Nilaparvata lugens upregulated the expression of AKT and InR and phosphorylation of AKT and FOXO proteins, thereby affecting the synthesis of 20E and JH and increasing the fecundity of females (Kang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Pooraiiouby et al (2018) found that a high‐carbohydrate food source significantly induced the expression of ILP3 in A. aegypti and increased the storage of nutrients to enhance the fecundity of female mosquitoes. Similarly, under high‐nutrient concentrations, Nilaparvata lugens upregulated the expression of AKT and InR and phosphorylation of AKT and FOXO proteins, thereby affecting the synthesis of 20E and JH and increasing the fecundity of females (Kang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a consensus has been reached regarding the fact that the resource allocation strategies and mechanisms present in different growth and dietary conditions are key aspects in the determination of an organism’s phenotypic specificities [ 1 , 2 ], including metabolism and even biomass composition [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These insects, belonging to diverse orders, are especially vulnerable to the challenges posed by seasonal shifts. Physiological constraints can be imposed due to temperature and water availability fluctuations (Tougeron et al 2020), as well as changes in the availability of nutrients required for individual development and reproduction (Kang et al 2022). However, ecologically and taxonomically, different groups cannot be expected to respond similarly to climate variables and changes in agricultural practices (Cameron et al 2019;Le Provost et al 2021).…”
Section: Introductionmentioning
confidence: 99%